The Impact of Participants’ Motivations for Engaging in Physical Activity on Their Reaction Time (Baltic Journal of Sport and Health Sciences, 2026)
Reaction time (RT) is a measure of the time elapsed between the application of a stimulus and the subsequent response. It is considered an indirect indicator of the central nervous system’s processing speed. Various factors, including body weight and physical activity, influence RT. Another factor that has not been investigated before is the effect of motivations for engaging in physical activity on motor reaction time, as measured by simple reaction time and recognition scores, indicated by the number of hits. Thus, the current study aimed to examine the impact of motivation in physical activity on RT and the number of hits. The study was conducted on 60 healthy volunteers aged 18–60 years (mean ± SD, 27.66 ± 8.31 years) who participated in regular physical activity. A headset for the virtual reality base station, controllers, and the Rezzil game were used to determine the RT. Additionally, the participants’ motives for engaging in physical activity were recorded using the Leisure Motivation Scale. It was found that the RT of participants was influenced by different leisure motivation categories, particularly for males. Body mass index (BMI) also affected the RT of participants, especially in the normal and overweight groups. However, the number of hits was not influenced by such motivations. These results showed that their motivations could influence the RT of individuals who participate in physical activity. Intrinsic motivations for physical activity, like personal enjoyment, reported slower RT than extrinsic motivations like ego or competition.Keywords: BMI, gender, motivation, physical activity, reaction time